2017
DOI: 10.1093/pcp/pcx114
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatin Synthase has Contrasting Effects on Cadmium and Arsenic Accumulation in Rice Grains

Abstract: Phytochelatin (PC) synthesis has been well demonstrated as a major metal tolerance mechanism in Arabidopsis thaliana, whereas its contribution to long-distance element transport especially in monocots remains elusive. Using rice as a cereal model, we examined physiological roles of Oryza sativa phytochelatin synthase 1 (OsPCS1) in the distribution and detoxification of arsenic (As) and cadmium (Cd), two toxic elements associated with major food safety concerns. First, we isolated four different transcript vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…2), which are known to play a critical role in the detoxification of Cd via complexation of the toxic ion (Cobbett & Goldsbrough, 2002). Mutation of PC synthase genes in Arabidopsis and rice leads to hypersensitivity to Cd (Howden et al, 1995b;Uraguchi et al, 2017), whereas overexpression of PC synthase genes or the activation of the GSH-dependent pathway can enhance Cd tolerance (Brunetti et al, 2011;Chen et al, 2015Chen et al, , 2016. Increased Cd accumulation in the roots of cadt1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), which are known to play a critical role in the detoxification of Cd via complexation of the toxic ion (Cobbett & Goldsbrough, 2002). Mutation of PC synthase genes in Arabidopsis and rice leads to hypersensitivity to Cd (Howden et al, 1995b;Uraguchi et al, 2017), whereas overexpression of PC synthase genes or the activation of the GSH-dependent pathway can enhance Cd tolerance (Brunetti et al, 2011;Chen et al, 2015Chen et al, , 2016. Increased Cd accumulation in the roots of cadt1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both the Arabidopsis thaliana GSH‐ and PC‐deficient mutants are highly sensitive to Cd (Howden et al , 1995a,b). The rice PCS1 mutants are also more sensitive to Cd (Uraguchi et al , ). Treatments of plant roots with buthionine‐sulphoximine, an inhibitor of GSH synthesis, also caused Cd sensitivity (Cobbett et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Uraguchi et al. () also isolated additional OsPCS2 variants, which were designated as OsPCS1 variants in their article, having a different transcription start site, and they reported that the longest OsPCS2 variant, OsPCS1full , showed the highest abundance among OsPCS transcripts. In contrast, Das et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenotypes were observed for other mutants involved in PC synthesis and transport. Recently, it was reported that the T‐DNA mutant of OsPCS2 showed a weak phenotype under Cd stress, in contrast to a clear decrease in As tolerance (Uraguchi et al., ). In addition, the knockout of OsABCC1 did not affect Cd toxicity in rice (Song et al., ), in contrast to Arabidopsis atabcc1 atabcc2 mutant showing high sensitivity to As and Cd (Park et al., ; Song et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported alternatively spliced transcripts of rice OsPCS2 gene to be involved in alleviation of Cd and As stresses in a tissue-specific way [62]. In another recent work, four rice OsPCS1 transcript variants and one OsPCS2 were isolated and their expression in PCS-deficient Arabidopsis and Schizosaccharomyces pombe mutants revealed PCS activity in response to Cd and As in the longest PCS1 variant, OsPCS1full [63]. In this regard, it was quite possible that the evolutionary forces could attribute exon-intron variations between monocot and dicot species.…”
Section: Sequence Analysis Of Pcssmentioning
confidence: 97%